Journal of Applied Informatics and Technology (Editorial Note) - Journal of Applied Informatics and Technology (Journal of Applied Informatics and Technology, 2025)
The Journal of Applied Informatics and Technology (JIT) has published Volume 7, Number 2 (2025): July-December, comprising a total of 15 research articles—ten in English and five in Thai. Each article has undergone peer review by at least three experts from different institutions. The authors revised their articles based on the reviewers’ comments until they were approved for publication. The editorial team also verified the accuracy of the content, references, and language usage to ensure the highest quality. We sincerely thank all the reviewers for their valuable feedback and thoughtful recommendations. The following articles have been published in Volume 7, Number 2 (2025): 1) Warfarin Care: Warfarin Management System for Older Adults Author: Narit Hnoohom, Konlakorn Wongpatikaseree, Autchariya Poungkaew, Junporn Kongwatcharapong (Hnoohom et al., 2025) 2) Measuring Neck Abnormalities for Preliminary Assessment of Neck Pain Disease using Virtual Reality Author: Manatsawee Sidajan, Kawintra Sittikraipong, Peerapat Kusumannukul, Sasiwimon Pornwachirawit, Waichaya Suwannakeeree, Sutasinee Jitanan (Sidajan et al., 2025) 3) An In-House Time Tracking Application Development with a Low-To-No-Code Platform Author: Sorn Tanharaphan, Thanabadee Rodvanich, Yatawee Aupasao, Natsuda Kaothanthong (Tanharaphan et al., 2025) 4) Leveraging PyThaiNLP for Sentiment Analysis of Thai Online Text: A Comparative Study of Logistic Regression and Support Vector Machine Author: Sunisa Duangtham, Setthaphong Lertritrungrot, Nattavadee Hongboonmee, Wansuree Massagram (Duangtham et al., 2025) 5) The Flood Simulation System as a New Process for Public Participation of Local Administrative Organizations in Tha Wang Pha District, Nan Province Author: Chamnan Kumsap, Vissanu Mungkung, Lanyanat Patanan, Phimraphas Ngamsantivongsa, Arisara Charoenpanyanet, Phonpat Hemwan (Kumsap et al., 2025) 6) Classification of Guanxi Mandarin Orange Grades using Machine Vision Algorithms Author: Fulian Huang, Jialin Xie, Shijun Jie, Nattawoot Suwannata (Huang et al., 2025) 7) Development and Cost-Effectiveness Analysis of a Fogging Pump Control System Commercial Prototype for Oyster Mushroom Cultivation based on Open-System Greenhouse Author: Non Pinngern, Bhannawat Wanganusorn (Pinngern & Wanganusorn, 2025) 8) Web Scraping-based System for E-commerce Price Comparison and Similar Product Segmentation Author: Pongsin Jankaew, Wachirawut Thamviset (Jankaew & Thamviset, 2025) 9) A Comparative Study of Sea Lettuce Cultivation in Seawater and Scientific Saltwater using IoT Technology Author: Suttipong Klongdee, Sriwaree Sujaritchai, Sommart Promput (Klongdee, Sujaritchai, & Promput, 2025) 10) Utilizing Association Rule Mining to Understand Phishing Risk Awareness Levels of Thai University Academic Staff Author: Pita Jarupunphol, Wipawan Buathong (Jarupunphol & Buathong, 2025) 11) Approximate String Matching Algorithm using Single Inverted Lists Author: Soontaree Thumsuwan, Nuanprang Sangurai, Chouvalit Khancome (Thumsuwan, Sangurai, & Khancome, 2025) 12) Pneumonia Detection from Chest X-ray Images using Convolutional Neural Networks and Transfer Learning Techniques Author: Pongsathorn Chedsom (Chedsom, 2025) 13) Feature Selection with Linear Discriminant Analysis to Improve the Performance of Heart Disease Classification Author: Ratiporn Chanklan, Keerachart Suksut, Kedkarn Podhijittikarn (Chanklan, Suksut & Podhijittikarn, 2025) 14) Information System for Wet Garbage Bin Data Management in Local Areas: A Case Study of Langu Subdistrict Administrative Organization, Satun Province Author: Norathep Sakphet, Chatirot Jitrugtham, Annop Bunjan, Kullaphat Yingdumnoon, Sakan Rodklai, Chanyanuch Pumpuang (Sakphet et al., 2025) 15) Rice Seed Production with Smart Farm Author: chalawan Wantong, Wanida Sumranram, Utis Tahom, Varit Kitthanarut, Ekkaluk Salukkham (Wantong et al., 2025) The editorial board of JIT sincerely hopes that the 15 articles published in this issue will benefit researchers and serve as a valuable source of knowledge for the advancement of their work. We believe that the insights and findings presented in this issue will contribute to academic and practical developments in the fields of informatics and technology. We warmly invite scholars, practitioners, and students to explore the articles and apply the knowledge gained to their own research and professional activities. Assoc. Prof. Olarik Surinta, Ph.D. Editor-in-Chief